The Effectiveness of Mindfulness-Based Sex Therapy on Sexual Self-Efficacy and Sexual Quality of Life in Couples - Ahmadzadeh , Hosna; Azadyekta , Mehrnaz; Bagheri , Fariborz (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aims to evaluate the effectiveness of mindfulness therapy-based sex therapy in improving sexual self-efficacy and sexual quality of life in couples experiencing sexual dysfunction.Methods and Materials: A quasi-experimental design with a control group and an experimental group was employed. The study sample consisted of 30 couples (15 couples in each group) experiencing sexual dysfunction, who were recruited from counseling centers in Karaj, Iran. The experimental group underwent 8–10 sessions of mindfulness therapy-based sex therapy, while the control group received no intervention. Data were collected using two validated instruments: the Sexual Self-Efficacy Questionnaire and the Sexual Quality of Life Questionnaire. Data analysis was conducted using SPSS version 24, with multivariate analysis of covariance (MANCOVA) to assess the effectiveness of the intervention.Findings: The results showed that the experimental group demonstrated significant improvements in both sexual self-efficacy and sexual quality of life from pre-test to post-test and follow-up, compared to the control group. The differences between pre-test and post-test scores in the experimental group were statistically significant (p < 0.001) and remained stable during the follow-up phase. The control group showed minimal changes over time. These findings suggest that mindfulness therapy-based sex therapy effectively enhances both sexual self-efficacy and quality of life in couples with sexual dysfunction.Conclusion: Mindfulness therapy-based sex therapy is a promising intervention for improving sexual self-efficacy and quality of life in couples facing sexual dysfunction. By addressing cognitive mindfulnesss, mindfulness, and emotional expression, the therapy provides comprehensive support for overcoming sexual challenges and enhancing relational satisfaction.